Inhibition characteristics of a novel PAM/SA-Ca(OH)2 composite inhibitor to control coal spontaneous combustion. (15th April 2022) - Huang, Zhian; Wang, Guanhua; Zhang, Yinghua; Yin, Yichao; Hu, Xiangming; Gao, Yukun; Yang, Yifu; Xin, Haihui
Highlights: This research mainly studied a novel PAM/SA-Ca(OH)2 composite inhibitor. Inorganic nanoparticles are combined with polyacrylamide by intercalation method. Functional group analysis proved excellent inhibition effects. Physical, chemical and composite inhibition mechanism was analyzed. Abstract: In order to overcome the short service life of existing inhibitors, the physical inhibitor polyacrylamide (PAM) and the nanomaterial silica aerogel powder (SA) were selected to intercalate a composite inhibitor. The product was a polymer-based composite (PAM/SA). Thereafter, PAM/SA was combined with the chemical inhibitor Ca(OH)2 to form a polymer-based composite inhibitor. Scanning electron microscopy revealed a significant increase in the number of folds and pores on the surface of PAM/SA. Through differential scanning calorimetry, it can be concluded that the thermal stability of PAM/SA was improved, and its glass transition temperature increased from 159 °C to 197 °C. In a thermogravimetric analysis, all characteristic temperature points of the coal samples treated with a composite inhibitor were found to have increased as compared to those treated with a single inhibitor. The thermogravimetric analysis demonstrated that the optimal ratio of PAM/SA to Ca(OH)2 was 1:1, and the activation energy of the treated coal sample increased from 326.74 KJ·mol −1 to 510.89 KJ·mol −1 . Through infrared spectroscopy, it was found that inhibition treatment can reduce reactive groups, such as hydroxyl and aliphatic hydrocarbons, and increase stable structural ether bonds. The above results show that a polymer-based composite inhibitor prepared using the intercalation method can better inhibit the coal spontaneous combustion.